Combining Statistical Analysis and Machine Learning for EEG Scalp Topograms Classification - Kuc, Alexander; Korchagin, Sergey; Maksimenko, Vladimir A.; Shusharina, Natalia; Hramov, Alexander E. (Frontiers in Systems Neuroscience, 2021)
Incorporating brain-computer interfaces, BCIs into daily life requires reducing the reliance of decoding algorithms on the calibration or enabling calibration with the minimal burden on the user. A potential solution could be a pre-trained decoder demonstrating a reasonable accuracy on the naive operators. Addressing this issue, we considered ambiguous stimuli classification task and trained an artificial neural network to classify brain responses to the stimuli of low and high ambiguity. We built a pre-trained classifier utilizing time-frequency features corresponding to the fundamental neurophysiological processes shared between subjects. To extract these features, we statistically contrasted EEG spectral power between the classes in the representative group of subjects. As a result, the pre-trained classifier achieved $74%$ accuracy on the data of newly recruited subjects. Analysis of the literature suggested that a pre-trained classifier could help naive users to start using BCI bypassing training and further increased accuracy during the feedback session. Thus, our results contribute to using BCI during paralysis or limb amputation when there is no explicit user-generated kinematic output to properly train a decoder. In machine learning, our approach may facilitate the development of transfer learning methods for addressing the cross-subject problem. It allows extracting the interpretable feature subspace from the source data (the representative group of subjects) related to the target data (a naive user), preventing the negative transfer in the cross-subject tasks.